Cardiac care of children with dystrophinopathy and females carrying DMD-gene variations. Issue 2 (17th October 2022) - Bourke, John; Turner, Cathy; Bradlow, William; Chikermane, Ashish; Coats, Caroline; Fenton, Matthew; Ilina, Maria; Johnson, Alexandra; Kapetanakis, Stam; Kuhwald, Lisa; Morley-Davies, Adrian; Quinlivan, Ros; et al.
Abstract : Objective: We provide succinct, evidence-based and/or consensus-based best practice guidance for the cardiac care of children living with Duchenne muscular dystrophy (DMD) as well as recommendations for screening and management of female carriers of mutations in the DMD -gene. Methods: Initiated by an expert working group of UK-based cardiologists, neuromuscular clinicians and DMD-patient representatives, draft guidelines were created based on published evidence, current practice and expert opinion. After wider consultation with UK-cardiologists, consensus was reached on these best-practice recommendations for cardiac care in DMD. Results: The resulting recommendations are presented in the form of a succinct care pathway flow chart with brief justification. The guidance signposts evidence on which they are based and acknowledges where there have been differences in opinion. Guidelines for cardiac care of patients with more advanced cardiac dystrophinopathy at any age have also been considered, based on the previous published work of Quinlivan et al and are presented here in a similar format. The recommendations have been endorsed by the British Cardiovascular Society. Conclusion: These guidelines provide succinct, reasoned recommendations for all those managing paediatric patients with early or advanced stages of cardiomyopathy as well as females with cardiac dystrophinopathy. The hope is that this will result in more uniform delivery of high standards of care for children with cardiac dystrophinopathy, so improving heart health into adulthood through timely earlier interventions across the UK.